Cultivating a math coaching practice a guide for K-8 math educators - Morse, Amy.; Schifter, Deborah; Sage eBooks (Thousand Oaks, Calif. : Corwin ; London : SAGE, 2009)
Amy Morse offers math activities, planning activities, & a facilitator's guide for developing mathematics leaders' coaching practice & knowledge of math teaching & learning.
"A joint publication with the Education Development Center."
Specialized.
Description based on print version record.
Keywords: Mathematics -- Study and teaching (Elementary); Mathematics -- Study and teaching (Secondary); Mathematics teachers -- Training of; Electronic books